2018
DOI: 10.2478/rjti-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of Method to Synthesize the Track Vertical Irregularities

Abstract: The paper focuses on the experimental verification of the results derived from numerical simulations, based on a model of the bogie-track system, where the vertical track irregularities are introduced in the form of a pseudorandom function. This function comes from an original method of synthesizing the vertical track irregularities, depending on the geometric quality of the track and on the velocity. To verify the method, the root mean square (RMS) of the simulated accelerations in the axles and the bogie fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The RMS acceleration is also marked on the diagrams. In all the cases presented, it is observed that the RMS The accelerometers were mounted on a side of the bogie as follows: one accelerometer on each axle box and one accelerometer on the bogie frame against each axle (Figures 2 and 3) [30][31].…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
“…The RMS acceleration is also marked on the diagrams. In all the cases presented, it is observed that the RMS The accelerometers were mounted on a side of the bogie as follows: one accelerometer on each axle box and one accelerometer on the bogie frame against each axle (Figures 2 and 3) [30][31].…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
“…The method to synthesize the vertical track irregularities [56,57] relies on the power spectral density of the track irregularities, as described by ORE B176 [59] and the The coupling effects between the wheels due to the propagation of the bending waves through the rails are neglected, and an equivalent model with concentrated parameters is adopted for the track. Against each wheelset j and j + 1, respectively, of the bogie i, the track is represented with a one-degree freedom system on the vertical direction, the corresponding displacement being z rj,j+1 , with j = 2i − 1 and i = 1, 2.…”
Section: Synthesizing Of the Vertical Track Irregularitiesmentioning
confidence: 99%
“…The method to synthesize the vertical track irregularities [56,57] relies on the power spectral density of the track irregularities, as described by ORE B176 [59] and the specifications stipulated by the UIC 518 Leaflet [60] concerning the track geometry quality in the testing and homologation of the railway vehicles from the perspective of the dynamic behaviour. According to this method, the vertical track irregularities are described via a pseudo-random function.…”
Section: Synthesizing Of the Vertical Track Irregularitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The localization of the track irregularities is presented in [21] by using the time and distance measurements.…”
Section: Introductionmentioning
confidence: 99%